DIAGNOSIS IN PEDIATRIC NEUROLOGY - Valeriu Popescu; Andrei Zamfirescu (Amaltea Medical Publishing House, 2009)
In this article, the authors present the important steps for the diagnosis of neurologic diseases in children. Simptoms and algorhitmic approach are discussed regarding for age and frequency of the neurological disturbances. The main features are reviewed in the following situations: neonatal neurologic distress and seizures, hypotonia, epileptic seizures and epileptic syndromes, cerebal palsy, abnormal gait, coma, mental retardation, abnormal behavior and communication, cranial nerve palsy, orthopedic abnormalities of neurologic etiology.